2020
DOI: 10.3389/fphys.2020.00780
|View full text |Cite
|
Sign up to set email alerts
|

Ectodermal Organ Development Is Regulated by a microRNA-26b-Lef-1-Wnt Signaling Axis

Abstract: The developmental role of Lef-1 in ectodermal organs has been characterized using Lef-1 murine knockout models. We generated a Lef-1 conditional over-expression (COEL) mouse to determine the role of Lef-1 expression in epithelial structures at later stages of development after endogenous expression switches to the mesenchyme. Lef-1 over expression (OE) in the oral epithelium creates a new dental epithelial stem cell niche that significantly increases incisor growth. These data indicate that Lef-1 expression is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The PMIS system can be used to specifically inhibit target miR function through seed sequence recognition. 20 , 21 , 22 , 23 In order to inhibit the different miRs in the miR-17-92 cluster, different PMIS constructs were designed to target the seed region of miR-17 , miR-18a , miR-19a , and miR-92a-1 , and stable cell lines were created by infecting SW579 with PMIS lentivirus constructs expressing GFP. As a control, we used the SW579 cell line expressing a PMIS empty vector, which does not inhibit miR function.…”
Section: Resultsmentioning
confidence: 99%
“…The PMIS system can be used to specifically inhibit target miR function through seed sequence recognition. 20 , 21 , 22 , 23 In order to inhibit the different miRs in the miR-17-92 cluster, different PMIS constructs were designed to target the seed region of miR-17 , miR-18a , miR-19a , and miR-92a-1 , and stable cell lines were created by infecting SW579 with PMIS lentivirus constructs expressing GFP. As a control, we used the SW579 cell line expressing a PMIS empty vector, which does not inhibit miR function.…”
Section: Resultsmentioning
confidence: 99%
“…We next determined if dental epithelial cell proliferation was affected in the lower incisor of Hmgn2 −/− embryos. We have previously shown that Pitx2 and Lef-1 control dental epithelial cell proliferation and differentiation ( 24 , 25 , 49 ). Our hypothesis is that the loss of Hmgn2 would increase the transcriptional activity of factors involved in dental epithelial cell proliferation and differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that FOXP4 positively regulated the expression levels of G1/S-specific cyclin-D1 (CCND1), JUN, MYC and MMP7 ( Fig. 4H ), which are well-established downstream target genes of the Wnt pathway ( 18 ). Collectively, these data suggested that FOXP4 activates the Wnt signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The current study verified that FOXP4 directly targeted the LEF-1 promoter and regulated its transcriptional activity, as confirmed via ChIP and luciferase reporter assays. LEF-1 is a member of the LEF/TCF transcription factor family and is a well-known binding partner of β-catenin, which promotes the activation of Wnt signaling ( 18 ). Whether FOXP4 exerted its carcinogenic effect via regulating Wnt signaling was further examined in the present study by measuring the expression levels of the Wnt/β-catenin signaling-related target genes.…”
Section: Discussionmentioning
confidence: 99%